GE_GERICHTE P/12749/2025 vom 5. November 2025 - GE Cour de justice (2025)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;LÉSION CORPORELLE PAR NÉGLIGENCE;RÈGLE DE LA CIRCULATION | CPP.310; CP.125; LCR.90.al1; LCR.26.al1; LCR.91.al2.letb